The last fashion house in Paris - Ryan, Renee (Love Inspired, 2024)
"France, 1942. Once, Paulette Leblanc spent her days flirting, shopping and drawing elegant dresses in her sketch pad. Then German tanks rolled into France, and a reckless romance turned into deep betrayal. Blaming herself for her mother's arrest by the Gestapo, Paulette is sent away to begin a new life in Paris, working as apprentice to fashion designer Sabine Ballard. But Maison de Ballard is no ordinary fashion house. While seamstresses create the perfect couture gowns, clandestine deals and secrets take place out of sight. Mademoiselle Ballard is head of a vast network of resistance fighters--including Paulette's coworker and friend Nicolle Cadieux--who help escort downed military men and Jewish families to safety. Soon Paulette is recruited as a spy. Working as a seamstress by day, gathering information at glamorous parties by night, Paulette at last has a chance to earn the redemption she craves. But as the SS closes in, and Nicolle goes missing, Paulette must make life-and-death decisions about who to trust, who to love and who to leave behind ..."--